Evaluation of a pharmacogenetic educational toolkit for community pharmacists. (September 2016) - Haga, Susanne B; Mills, Rachel; Moaddeb, Jivan
Aim: Over the past several decades, the roles and services of community pharmacists have expanded beyond traditional medical dispensation and compounding, and include health services such as vaccinations, and clinical testing and screening. Incorporating pharmacogenetic (PGx) testing into the menu of pharmacy services is logical and feasible; however, few pharmacists have experience with PGx testing, and few educational resources about PGx are available to support the uptake of PGx testing in community pharmacies.Methods: We developed a toolkit of four resources to assist pharmacists to provide PGx testing. We conducted a survey of pharmacists in North Carolina to evaluate each component of the toolkit and the toolkit as a whole.Results: A total of 380 respondents completed the evaluation of one or more toolkit components (344 evaluated all four components and the overall toolkit). Most respondents (84%) have never ordered or used PGx test results. Though the usability of the toolkit overall was below average (65.1 on a range of 0–100), individual components were perceived as useful and more than 75% of pharmacists reported that they would use the toolkit components when offering testing, with the result summary sheet receiving the highest score (4.01 out of 5). Open-text comments highlighted the need for more patient-friendly language and formatting.Conclusion: The majority of pharmacist respondents scored the components of the toolkit favorably. The next steps will be to revise and assess use of the toolkit in community pharmacy settings.